Antimicrobial activity and thermal stability of rosemary essential oil:β−cyclodextrin capsules applied in tomato juice - Ayala Zavala, Jesus Fernando (2019)
Rosemary essential oil (RO) was encapsulated within β-cyclodextrin (β-CD) to offer thermal stability and preserve its antimicrobial activity. The identified RO volatiles were 1,8 cineole (52%), 3-carene (9.6%), and camphor (9.3%). The growth of Salmonella Typhimurium, Listeria monocytogenes, Candida tropicalis, and Saccharomyces pastorianus was inhibited by 10, 10, 4.5, and 1.5 mg of free RO per mL of media, respectively. However, RO exhibited its evaporation at 43 °C, losing 50% of its weight at 100 °C and decomposing at 130 °C. RO:β-CD, at a 16:84 wt ratio, showed the highest presence of RO volatiles (7.33 g of RO/100 g of capsules) and initiated its decomposition at 75 °C, accompanied by a 10% weight loss. These particles underwent decomposition at 290 °C. Infrared analysis of RO:β-CD showed molecular interactions between RO and β-CD. The minimal inhibitory concentrations of the encapsulated RO for S. Typhimurium, L. monocytogenes, C. tropicalis, and S. pastorianus were 14.66, 14.14, 2.05, and 3.07 mg/mL, respectively. RO capsules were stable during tomato juice pasteurization and maintained their antimicrobial activity. In conclusion, the encapsulation of RO by β-CD offered protection to the volatile constituents exposed to high temperatures and maintained its antimicrobial properties after the encapsulation process and pasteurization of tomato juice.